The Effect of Destination Management and Community Participation to The Visitors Consumption at Tebing Breksi Sleman Yogyakarta - Ashartono, Rakhmat; Rahmanita, Myrza; Lemy, Diena Mutiara (Institut Pariwisata Trisakti, 2018)
The development of a new tourist destination indeed needs more attention to increase the number of tourist arrivals coming in an area. Breksi Cliff is one of the new destinations in Sleman district which is in the development period, with the development of Breksi cliff is expected to increase the level of welfare of the surrounding community through the development of the destination and community participation itself. This research is a research with descriptive method of analysis with quantitative approach to know accurate information about matters related to Tourism Destination Management and Public Participation to Welfare Society through Visitor Consumption. for the data analysis techniques alone will use Structural Equation Modeling. From the results of the study found that the level of community welfare Taman Tebing Breksi can increase with the management of destinations and community participation itself through the consumption of visitors